Induction of Systemic Resistance to Botrytis cinerea in Tomato by Pseudomonas aeruginosa 7NSK2: Role of Salicylic Acid, Pyochelin, and Pyocyanin - Kris Audenaert; Theresa Pattery; Pierre Cornelis; Monica Höfte (Molecular Plant-Microbe Interactions, 2002)
The rhizobacterium Pseudomonas aeruginosa 7NSK2 produces secondary metabolites such as pyochelin (Pch), its precursor salicylic acid (SA), and the phenazine compound pyocyanin. Both 7NSK2 and mutant KMPCH (Pch-negative, SA-positive) induced resistance to Botrytis cinerea in wild-type but not in transgenic NahG tomato. SA-negative mutants of both strains lost the capacity to induce resistance. On tomato roots, KMPCH produced SA and induced phenylalanine ammonia lyase activity, while this was not the case for 7NSK2. In 7NSK2, SA is probably very efficiently converted to Pch. However, Pch alone appeared not to be sufficient to induce resistance. In mammalian cells, Fe-Pch and pyocyanin can act synergistically to generate highly reactive hydroxyl radicals that cause cell damage. Reactive oxygen species are known to play an important role in plant defense. To study the role of pyocyanin in induced resistance, a pyocyanin-negative mutant of 7NSK2, PHZ1, was generated. PHZ1 is mutated in the phzM gene encoding an O-methyltransferase. PHZ1 was unable to induce resistance to B. cinerea, whereas complementation for pyocyanin production or co-inoculation with mutant 7NSK2-562 (Pch-negative, SA-negative, pyocyanin-positive) restored induced resistance. These results suggest that pyocyanin and Pch, rather than SA, are the determinants for induced resistance in wild-type P. aeruginosa 7NSK2.